The role of tourist experience, perceived value, and storytelling in brand value creation: A case study from Silancur Highland - Susanta, Susanta (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
Purpose – This research uses brand relationship theory as a theoretical framework for analyzing the role of the variables perceived value (PV), affective commitment (AC), and storytelling behavior (SB) to show the relationship between tourist experience (TE) and brand value (BV).Design/methodology/approach – The study approach was evaluated empirically using data from 175 Generation Z tourists visiting the desti¬nation Silancur Highland. The research model was tested using AMOS.Findings – The research results show that1). Tourist Experience has a significant and positive effect on perceived value. 2). Tourist Experience has a significant and positive effect on Affective Commitment. 3). Perceived value has a significant and positive effect on Affective commitment. 4). perceived value has a significant and positive effect on storytelling behavior. 5). affective commitment has a significant and positive effect on storytelling behavior. 6). Storytelling behavior has a significant and positive effect on brand value. 7). Tourist experience has a significant and positive effect on storytelling behavior. 8). Tourist experience has a significant and positive effect on brand value.Research limitations/implications – Researchers only replicate the model in various types of tourism, such as sport tourism, rural tourism, farm tourism, heritage tourism, and rural tourism, so it cannot yet generalize the results further. Future research can also apply this framework to the context of other fields of science such as communication as well as psychology and other consumer features.Practical implications – empirical investigation findings, management of this area is significant because this will determine how good the total brand value is. Managers must also be able to stand out from the crowd due to the intense competition. This can be achieved by developing a tourist experience that combines these elements to build customer brand relationships, which are important for growing brand value.Originality/value – This research is a pioneering use of brand relationship theory to explore the impact of tourist experience on affective commitment, storytelling behavior, and brand value at the destination Silancur Highland, provides a new view through empirical confirmation of a model that connects tourist experience activities with brand value through perceived value (PV), affective commitment (AC), and storytelling behavior (SB).